INTERAKSI SOSIAL ANGGOTA DEWAN DALAM PENYUSUNAN PERATURAN DAERAH DPRD KABUPATEN HALMAHERA SELATAN PROVINSI MALUKU UTARA - AMIHI, DEREIFEL; LENGKONG, FLORENCE DAICY; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2019)
Abstrack : At the level of making a rule, from the government side certainly considers the various policies issued such as Government Regulation. The Government Regulation is a legislation in Indonesia that set or issued by President to execute the rule as it should be. In Government Regulation material is a material to execute the constitution, of which inside the legislation was stated that the Government Regulation is an organic rule rather than constitution according to the hierarchy its should not overlap or be in contrast. The Government Regulation was made with purpose to restrain society of group and opinion freedom and also to fill in the blanks of rules that don’t exist yet. Local Parliament is regional people’s representative institutions who executes the Local Government function as the Regional Government Partners. And certainly in executing this function, there are also main duty and main function of the Local Parliament which of the duties and authorities was about: to form the Local Regulation about District Revenue and Expenditure Budget that submitted by the Regional Leader. And it is inseparable to be a supervision of the implementation of Regional Regulation and District Revenue and Expenditure Budget that submitted by the Regional Leader. And it has functions as Legislation Function, Budgeting Function, and Supervision Function.